Association between Biologic Outcomes and Objectively Measured Physical Activity Accumulated in ≥ 10-Minute Bouts and < 10-Minute Bouts - Loprinzi, Paul D.; Cardinal, Bradley J. (American journal of health promotion, 2013)
Purpose. Examine whether nonbout physical activity (i.e., <10 minutes' duration of physical activity [PA]) demonstrates a stronger association with health outcomes than bout physical activity (i.e., ≥ 10 minutes' duration). Design. Cross-sectional study. Setting. NHANES 2003–2006. Subjects. A total of 6321 participants ranging in age from 18 to 85 years. Measures. Objectively measured PA was assessed using accelerometry. A variety of health outcomes (e.g., triglyceride levels) were objectively measured, including an assessment of metabolic syndrome. Analysis. Multivariate regression analyses examined the association between bouts and nonbouts on each of the biologic health outcomes. Additionally, differences in each of the biologic variables among those who met PA guidelines for both approaches were evaluated. Results. After adjustments, results were similar for both approaches. For example, the odds ratio (OR) for metabolic syndrome for nonbouts (OR, 1.89; p < .001) was similar to that for bouts (OR, 1.87; p = .002). With the exception of body mass index, similar values for the biologic variables were found between those meeting guidelines for the two PA approaches. Conclusion. Engaging in nonbouts, as opposed to bouts of PA, is just as strongly associated with several biologic health outcomes, suggesting that adults who perceive themselves as having little time to exercise may still be able to enhance their health by adopting an active lifestyle approach.